2016
DOI: 10.1177/1029864916644486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of well-being of older adult choir singers and the general population in Finland: A case-control study

Abstract: Previous research suggests that singing in a choir as an older adult is associated with better quality of life (QOL). However, the degree to which sociodemographic variables and level of engagement in hobbies contribute to this relationship is largely unknown. The aim of the study was to compare quality of life (QOL) of older adult choir singers with a matched sample of older adults from the general population in Finland, taking into consideration sociodemographic, satisfaction with health, and level of engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
2
26
1
2
Order By: Relevance
“…This highlights subtle differences between the two concepts that require further research. For wellbeing, where there are existing studies to relate to, the lack of group differences found here contradicts earlier findings showing an advantage for music over other creative activities in terms of wellbeing and quality of life (Hallam and Creech 2016;Johnson et al 2017), but supports the general lack of global differences on other measures related to wellbeing such as anxiety and depression (Pearce et al 2016). Although fewer of our participants chose to knit in groups (17.5% compared to 50% in Riley et al 2013), the lack of any influence of group activity on happiness or wellbeing also counters earlier evidence that group knitters experienced more positive emotions (Riley et al 2013), while the clear positive relationship found here between age, happiness and subjective wellbeing confirms earlier findings that older participants report higher levels of happiness (Blanchflower and Oswald 2008;Diener et al 1999;López Ulloa et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This highlights subtle differences between the two concepts that require further research. For wellbeing, where there are existing studies to relate to, the lack of group differences found here contradicts earlier findings showing an advantage for music over other creative activities in terms of wellbeing and quality of life (Hallam and Creech 2016;Johnson et al 2017), but supports the general lack of global differences on other measures related to wellbeing such as anxiety and depression (Pearce et al 2016). Although fewer of our participants chose to knit in groups (17.5% compared to 50% in Riley et al 2013), the lack of any influence of group activity on happiness or wellbeing also counters earlier evidence that group knitters experienced more positive emotions (Riley et al 2013), while the clear positive relationship found here between age, happiness and subjective wellbeing confirms earlier findings that older participants report higher levels of happiness (Blanchflower and Oswald 2008;Diener et al 1999;López Ulloa et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Pearce and colleagues compared newly-formed singing, creative writing and crafting groups, finding more rapid social bonding in the music group (Pearce et al 2015) but no group differences after 7 months on wellbeing measures (Pearce et al 2016). Johnson et al (2017) found higher levels of physical (but not psychological) quality of life in older adult choir singers compared to other older adults, including those involved in other hobbies. Similarly, older people involved in music projects scored more highly on wellbeing and perceived cognitive, health and emotional measures compared with those taking craft, yoga or language lessons (Hallam and Creech 2016).…”
mentioning
confidence: 99%
“…Az idős ember életében hosszú ez a közös idő, így a kapcsolat mélyül a látvány által is. A látvány vonalszerkezete és színgazdagsága, a színek harmóniája ebben döntő szerepet játszik (Itten 1978). Az otthon tudatos kialakítása identitásunk részévé teszi (place-identity, Proshansky 1983), az lesz számunkra a "térbeli mag" (territorial core, Porteous 1976).…”
Section: Követlen Környezetunclassified
“…One study presented suggests that older adults with 10 or more years of musical experience throughout their lifetime perform better on tests of executive function and nonverbal memory than those without musical experience (Hanna-Pladdy and MacKay, 2011), supporting the idea that musical training can confer a cognitive reserve during the aging process. Perhaps fortunately, for those without earlier musical training, recent studies demonstrated the benefits of participation in choir singing on the health and well-being of older adults (Johnson et al, 2017). In addition, the panel discussed the role music might play in the development of hearing loss therapies and that participation in creative musical activities (such as improvisation) may protect against age-related cognitive decline.…”
Section: Music As a Therapeutic Intervention In Adults: Overlapping Cmentioning
confidence: 99%